Mitigation of free radicals and carbohydrate-linked enzymes by extracts and partitioned fractions of Elephantorrhiza elephantina (Burch.) Skeels root - Lebohang D. Moloi; Fatai O. Balogun; Anofi O.T. Ashafa (AOSIS, 2021)
Background: Elephantorrhiza elephantina (Burch.) Skeels is a medicinal plant used in folkloric medicine for the management of several metabolic and infectious diseases. Aim: This aim of this research study was to investigate the antioxidant and antidiabetic effects of extracts and partitioned fractions in order to validate its folkloric use. Setting: The plant material purchased from herb sellers in Qwaqwa township, authenticated at Department of Plant Science Qwaqwa herbarium, was evaluated in the same unit of the University of the Free State. Methods: The antioxidative and antidiabetic activities of extracts and fractions were assessed with 1,1-diphenyl-2-picrylhydrazyl, 2,2-azino-bis(3-ethylbenzothiazoline-6)-sulphonic acid, hydroxyl radicals, metal chelating agents, and α-amylase, as well as α-glucosidase inhibitions based on standard methods. The subfractions with considerable yields from the partitioned n-hexane fraction of the crude extract were subjected to gas chromatography-mass spectrometry analysis or profiling for possible compound identification. Results: The aqueous extract showed the most effective 1,1-diphenyl-2-picrylhydrazyl, hydroxyl radical and metal chelating activities judging by half-maximal inhibitory concentrations (IC50: 0.573, 0.059 and 1.937 mg/mL, respectively), whilst the ethanol extract revealed maximum activity (0.017 mg/mL) against 2,2-azino-bis(3-ethylbenzothiazoline-6)-sulphonic acid. However, the ethanol extract displayed the most potent alpha-amylase (0.346 mg/mL) inhibition, whilst the aqueous extract (0.363 mg/mL) was best against alpha-glucosidase. The modes of enzymes inhibition revealed that the aqueous extract displayed near-competitive inhibition against alpha-amylase and uncompetitive inhibition against alpha-glucosidase. Additionally, good antioxidative and antihyperglycaemic effects were established by the n-hexane fraction when compared with standards (gallic acid and acarbose). The GC-MS chromatogram of subfractions (4 and 9) from the n-hexane fraction afforded compounds, such as 2,4-bis (1, 1-dimethylethyl)-phenol, 9-octadecenoic acid (Z)-, methyl ester, dodecanoic acid and 1-methylethyl ester already established in the literature with potential pharmacological activities (antioxidant, anti-inflammatory, etc.). Conclusion: The research study provides evidence on the folkloric use and insights on the prospect of the plant as natural antioxidative and antidiabetic agents.